2008
DOI: 10.1063/1.2956396
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue damage characterization using surface acoustic wave nonlinearity in aluminum alloy AA7175-T7351

Abstract: Nonlinear ultrasonic (NLU) harmonic generation system was used to characterize the fatigue damage in a flat hour-glass, high strength Al–Cu–Zn–Mg alloy, AA7175-T7351 specimens. Experiments were carried out to introduce controlled levels of fatigue damage under constant amplitude loading to determine the NLU response using surface acoustic wave (or Rayleigh mode) at regular intervals of fatigue life. The NLU parameter (A2/A12) plotted as a function of percentage of fatigue life shows two peaks for all the sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 28 publications
1
12
1
Order By: Relevance
“…INTRODUCTION In past decades, the study of nonlinear elastic wave propagation has been of considerable interest, which is due to the fact that nonlinear parameters are generally more sensitive to the changes in the microstructure than linear ones (velocity and attenuation). [1][2][3][4][5] When a purely sinusoidal ultrasonic wave launched into a crystalline solid, the interaction of the acoustic wave with microstructures such as dislocations and precipitates would lead to distortion of the initial waveform and generation of higher harmonic waves. [6][7][8][9][10][11][12][13] Suzuki et al 6 predicted the generation of the secondharmonic of an ultrasonic wave propagating in a crystal due to glide motion of dislocations by using the dislocations string model.…”
mentioning
confidence: 99%
“…INTRODUCTION In past decades, the study of nonlinear elastic wave propagation has been of considerable interest, which is due to the fact that nonlinear parameters are generally more sensitive to the changes in the microstructure than linear ones (velocity and attenuation). [1][2][3][4][5] When a purely sinusoidal ultrasonic wave launched into a crystalline solid, the interaction of the acoustic wave with microstructures such as dislocations and precipitates would lead to distortion of the initial waveform and generation of higher harmonic waves. [6][7][8][9][10][11][12][13] Suzuki et al 6 predicted the generation of the secondharmonic of an ultrasonic wave propagating in a crystal due to glide motion of dislocations by using the dislocations string model.…”
mentioning
confidence: 99%
“…The most extensively used method in NDE is ultrasonic testing, which is effective because it has high mobility and high feasibility with a relatively simple instrumentation and uncomplicated configuration [6,7,10,11]. Particularly, the measurement of acoustic nonlinearity has shown its effectiveness in the evaluation of microstructural changes in materials, including stress corrosion cracks [12], plastic deformation [13][14][15][16], residual stress [17], fatigue [5,6,14,16,[18][19][20][21], thermal aging [4,8,9,[22][23][24][25][26], creep [10], and so on [18,27,28]. The microstructural changes, such as the evolution of dislocation structure, precipitate growth, and the phase transitions of precipitates, affect the acoustic nonlinearity of any ultrasonic waves propagating through the region where the microstructural change has taken place.…”
Section: Introductionmentioning
confidence: 99%
“…By monitoring the variations in the acoustic nonlinearity, the changes in the microstructure can be nondestructively evaluated. Several theoretical [5,8,18,29] and experimental [4][5][6][8][9][10][12][13][14][15][16][17][18]20,[22][23][24][25][26][27][28][29][30] studies have shown that the acoustic nonlinearity parameter can represent a sensitive indicator in the NDE of the material degradations.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic methods were often used for fatigue assessments by detecting acoustic nonlinearity, crack length, elasticity, and the accumulation of damage [6][7][8][9][10][11][12]. Laser ultrasonic (LU) techniques have demonstrated increasingly high capabilities in the nondestructive evaluation (NDE) of the mechanical properties of materials [13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%